Neuropeptide expression and morphometric differences in crushed alveolar inferior nerve of rats: Effects of photobiomodulation - Martins, Daniel Oliveira; Santos, Fabio Martinez dos; Ciena, Adriano Polican [UNESP]; Watanabe, Ii-Sei; Britto, Luiz Roberto G. de; Dias Lemos, Jose Benedito; Chacur, Marucia (Springer, 2017)
Inferior alveolar nerve (IAN) injuries may occur during various dental routine procedures, especially in the removal of impacted lower third molars, and nerve recovery in these cases is a great challenge in dentistry. Here, the IAN crush injury model was used to assess the efficacy of photobiomodulation (PBM) in the recovery of the IAN in rats following crushing injury (a partial lesion). Rats were divided into four experimental groups: without any procedure, IAN crush injury, and IAN crush injury with PBM and sham group with PBM. Treatment was started 2 days after surgery, above the site of injury, and was performed every other day, totaling 10 sessions. Rats were irradiated with GaAs Laser (Gallium Arsenide, Laserpulse, Ibramed Brazil) emitting a wavelength of 904 nm, an output power of 70 mWpk, beam spot size at target similar to 0.1 cm(2), a frequency of 9500 Hz, a pulse time 60 ns, and an energy density of 6 J/cm(2). Nerve recovery was investigated by measuring the morphometric data of the IAN using TEM and by the expression of laminin, neurofilaments (NFs), and myelin protein zero (MPZ) using Western blot analysis. We found that IAN-injured rats which received PBM had a significant improvement of IAN morphometry when compared to IAN-injured rats without PBM. In parallel, all MPZ, laminin, and NFs exhibited a decrease after PBM. The results of this study indicate that the correlation between the peripheral nerve ultrastructure and the associated protein expression shows the beneficial effects of PBM.
Keywords: Molecular changes; Alveolar inferior nerve; Photobiomodulation; Myelin sheath; Rat